Dengue uveitis - a major review - Xie, Amy Cen (2024)
Dengue fever is a significant global public health concern with increasing incidence over the past two decades. The symptoms range from mild to severe, including fever, headache, rash, and joint pain. Ocular complications are prevalent among hospitalized patients, estimated to be between 10% and 40.3%, with varying incidences based on the serotype and severity of dengue. These complications can be hemorrhagic or inflammatory and typically occur after the onset of fever. Modern diagnostic tools such as Optical Coherence Tomography (OCT) and Fundus Fluorescein Angiography (FFA) have enabled physicians to better understand the extent of ocular involvement and guide treatment. This article provides an updated overview of the various manifestations of dengue uveitis, including their diagnosis and treatment.